PENGARUH PENAMBAHAN LIMBAH B3 PADA KUAT BETON MUTU K-175 - Bobby Damara; Zulkifli Lubis (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2018)
Innovations of concrete growing quite rapidly now from reuse and reduce. materials unused or addition of additives in order to increase the quality of concrete include the addition of waste carbide (B3) is an effort to increase the element calcium is required in the reaction pozzolanic when mixed with SiO2 in the fly ash, Pozzolanic reaction is a reaction between calcium, silica or aluminates with water to form a strong and rigid mass similar to the cement hydration process. The mixing process carbide waste as a concrete material is done by laboratory testing in accordance with data from literature Indonesian Standard SK SNI and foreign standards are ASTM with variation of composition dregs carbide 5% as a substitute for cement material with a target quality of concrete K-175. From this result the composition of dregs addition of a mixture of dregs carbide 5% with an average compressive strength of 249,69 kg/cm2. That value greater than 1,77% of the normal concrete  245,36 kg/cm2.